1988
DOI: 10.1212/wnl.38.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of status epilepticus

Abstract: In a randomized, nonblinded clinical trial, 36 consecutive patients with generalized convulsive status epilepticus were treated with either combination diazepam and phenytoin (DZ/DPH) or phenobarbital (PB). Phenytoin was added to the PB regimen if seizures persisted for 10 minutes after beginning therapy. The cumulative convulsion time (total time spent in active convulsive movements) was shorter for the PB group than for the DZ/DPH group (median, 5 versus 9 minutes, p less than 0.06); the response latency (el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(136 citation statements)
references
References 0 publications
1
129
0
6
Order By: Relevance
“…Nine RCTs (three class I [22][23][24], one class II [25], and five class III [26][27][28][29][30]) addressed the efficacy of initial therapy. The 1998 Veteran's Affairs status epilepticus study was a multicenter randomized comparison of four different IV treatments: lorazepam (0.1 mg/kg), diazepam (0.15 mg/kg) followed by phenytoin (18 mg/kg), phenobarbital (18 mg/kg), and phenytoin alone (18 mg/kg) in adults with either overt or subtle status epilepticus (22).…”
Section: Q1 Which Anticonvulsants Are Efficacious As Initial and Submentioning
confidence: 99%
“…Nine RCTs (three class I [22][23][24], one class II [25], and five class III [26][27][28][29][30]) addressed the efficacy of initial therapy. The 1998 Veteran's Affairs status epilepticus study was a multicenter randomized comparison of four different IV treatments: lorazepam (0.1 mg/kg), diazepam (0.15 mg/kg) followed by phenytoin (18 mg/kg), phenobarbital (18 mg/kg), and phenytoin alone (18 mg/kg) in adults with either overt or subtle status epilepticus (22).…”
Section: Q1 Which Anticonvulsants Are Efficacious As Initial and Submentioning
confidence: 99%
“…Other shortcomings include adverse events, such as delirium and sedation should be remembered. Several randomized controlled trials support the use of diazepam and lorazepam as initial drug therapy in patients with status epilepticus (Shaner et al, 1988;Treiman et al, 1998;Alldredge et al, 2001). A randomized double-blind trial demonstrated the effectiveness of intravenous diazepam on status epilepticus when the drugs were administered by paramedics before patients arrived at the hospital (Alldredge et al, 2001).…”
Section: Benzodiazepines In the Intensive Care Unitmentioning
confidence: 99%
“…Results from four comparative studies have suggested that lorazepam is superior to phenytoin and as effective as clonazepam, diazepam, or the combination of diazepam and phenytoin in the initial treatment of status epilepticus (Sorel et al, 1981;Shaner et al, 1988;Treiman et al, 1998;Alldredge et al, 2001). Large lorazepam doses (0.3-9 mg/ h) have been used for treating refractory status epilepticus and lorazepam has been shown to terminate status epilepticus efficiently (Labar et al, 1994).…”
Section: Benzodiazepines In the Intensive Care Unitmentioning
confidence: 99%
“…Previous reports have been largely adult-based (Shaner et al 1988, Martin and Millac 1994, Walker et al 1995 frequently using different protocols. Although there is some information on children presenting to A and E, details of the drugs given and their doses were not included in these reports (Mathes and Wallace 1995, Scholtes et al 1996, Smith et al 1996.…”
Section: Discussionmentioning
confidence: 99%